2020
DOI: 10.1038/s41598-020-78612-8
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and non-thermal effects of capacitive–resistive electric transfer application on different structures of the knee: a cadaveric study

Abstract: Capacitive–resistive electric transfer therapy is used in physical rehabilitation and sports medicine to treat muscle, bone, ligament and tendon injuries. The purpose is to analyze the temperature change and transmission of electric current in superficial and deep knee tissues when applying different protocols of capacitive–resistive electric transfer therapy. Five fresh frozen cadavers (10 legs) were included in this study. Four interventions (high/low power) were performed for 5 min by a physiotherapist with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Previous studies have shown supraspinatus tendon properties and tendon assessment by elastography in healthy populations [ 13 , 14 , 15 , 16 , 17 ], presenting results that are in line with ours [ 17 , 18 ]. Differences in elastic properties of the tendon values are explained by blood perfusion and the consequent increase in temperature, with stiffer tissues presenting higher values on SEL measurement and softer tissues lower values on SEL measurement [ 9 , 12 , 34 ]. In this context, SEL supraspinatus mean values are known to be around 3.55 in subjects with supraspinatus tendinopathy, 3.75 in healthy subjects and 3.8 in a healthy sports population [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown supraspinatus tendon properties and tendon assessment by elastography in healthy populations [ 13 , 14 , 15 , 16 , 17 ], presenting results that are in line with ours [ 17 , 18 ]. Differences in elastic properties of the tendon values are explained by blood perfusion and the consequent increase in temperature, with stiffer tissues presenting higher values on SEL measurement and softer tissues lower values on SEL measurement [ 9 , 12 , 34 ]. In this context, SEL supraspinatus mean values are known to be around 3.55 in subjects with supraspinatus tendinopathy, 3.75 in healthy subjects and 3.8 in a healthy sports population [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a CRMR application has shown other effects, such as a greater effect on haemoglobin saturation [ 4 ], immunological responses [ 5 , 6 ] and changes in tendon elasticity but only in the short term [ 7 ]. In this regard, hyperthermia techniques appear to be promising as a way to increase vascularity; blood perfusion; temperature; and therefore, the viscoelasticity of the soft tissue, which is thought to be crucial in keeping the musculoskeletal system healthy and functional [ 7 , 8 , 9 ]. Thus, it is important to research techniques that try to reach this goal and to assess their effects on the tissue over time.…”
Section: Introductionmentioning
confidence: 99%
“…On this line, future studies must explain the dosage according to frequency of emission, the pulse of the signal (continuous or pulsed in a percentage of time), intensity and periodicity of treatment. Although tissue surface temperature could also be interesting to investigate, due to types of emission temperature differing significantly from surface to deeper tissues [ 41 ], the latter is the target of treatment in most cases.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the control of these reactions is still highly based on the empirical experience of the therapist [5,[16][17][18]. There are only two in vitro studies that analyzed changes in temperature and current flow in cadavers [13,19]. These studies analyzed these variables in the Achilles tendon and myotendinous junction [13] and in the different structures of the knee [19] by applying different capacitive and resistive programs at high and low powers for 5 min [13].…”
Section: Introductionmentioning
confidence: 99%
“…There are only two in vitro studies that analyzed changes in temperature and current flow in cadavers [13,19]. These studies analyzed these variables in the Achilles tendon and myotendinous junction [13] and in the different structures of the knee [19] by applying different capacitive and resistive programs at high and low powers for 5 min [13]. Nevertheless, no study to date has studied changes in current flow and temperature when a standardized treatment protocol for chronic elbow tendinopathy is applied.…”
Section: Introductionmentioning
confidence: 99%